170 SKELETAL MUSCLE LOSS DURING NEOADJUVANT CHEMOTHERAPY IS A PREDICTOR OF MAJOR POSTOPERATIVE COMPLICATIONS IN PATIENTS WITH ESOPHAGUS CANCER. (17th September 2021) - Higashizono, Kazuya; Sato, Shinsuke; Nagai, Erina; Taki, Yusuke; Nishida, Masato; Ohata, Kou; Kanemoto, Hideyuki; Watanabe, Masaya; Oba, Noriyuki
Abstract:  : It is known that various factors, including surgical stress, nutritional deficits and sarcopenia, affect the incidence of postoperative complications. The aim of this study is to identify the predictors of major complications (Clavien-Dindo ≥II) after esophageal resection following neoadjuvant chemotherapy (NAC). Methods: Forty-nine patients with esophageal cancer undergoing NAC and surgery between January 2017 and December 2019 were identified from our surgery database and retrospectively analyzed. Onodera prognostic nutritional index (PNI) was used as the indicator of nutritional status. For the evaluation of skeletal muscle mass, computed tomography imaging of the total cross-sectional muscle tissue measured at the third lumbar level defined the skeletal muscle index (SMI). Images were collected before and after NAC. Univariate and multivariate logistic regression analyses were used to assess the association between various predictors and major postoperative complications. Results: Of the Forty-nine patients, 20 patients (40.8%) had major complication after surgery. Of the 20 patients, 5 had pneumonia and 4 had anastomotic leakage. Nine patients (18.3%) complete planned dose of NAC. SMI reduction was observed in 42 patients (85.7%) during NAC. According to univariate analysis, SMI reduction during NAC, and PNI before chemotherapy were significantly associated with major postoperative complications (P = 0.032, P = 0.035, respectively). According to multivariate analysis, SMI reduction during NAC is an independent predictor for the incidence of major postoperative complications (P = 0.0034). Conclusion: Skeletal muscle loss during neoadjuvant chemotherapy can be an useful predictor of major postoperative complications in patients with esophageal cancer.